2020
DOI: 10.1523/eneuro.0468-19.2020
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Maturation and Attrition of Adult Neurogenesis in the Hippocampus

Abstract: Sex differences exist in the regulation of adult neurogenesis in the hippocampus in response to hormones and cognitive training. Here we investigated the trajectory and maturation rate of adult-born neurons in the dentate gyrus (DG) of male and female rats. Sprague-Dawley rats were perfused two hours, 24 hours, one, two or three weeks after BrdU injection, a DNA synthesis marker that labels dividing progenitor cells and their progeny. Adult-born neurons (BrdU/NeuN-ir) matured faster in males compared to female… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 73 publications
5
49
0
Order By: Relevance
“…Importantly, we found that the lowest dose of exposure significantly impaired neurogenesis in females, but only moderately in males, suggesting female mice may be more prone to HZE-induced insult to neurogenesis. Given that male rodents have been shown to develop greater maladaptive responses to HZE-exposure than females 38 and are generally more vulnerable to brain injury than females 39 , our results showing higher sensitivity in females is unexpected and may be reflective of a lower rate of baseline neurogenesis in female rodents 40 , 41 , which is also evident in our data. Remarkably though, the population of newly born neurons in both female and male mice, regardless of radiation dose, rebounded to significantly higher levels than sham-irradiated control levels when assayed later, at 12 months post-exposure.…”
Section: Discussionsupporting
confidence: 61%
“…Importantly, we found that the lowest dose of exposure significantly impaired neurogenesis in females, but only moderately in males, suggesting female mice may be more prone to HZE-induced insult to neurogenesis. Given that male rodents have been shown to develop greater maladaptive responses to HZE-exposure than females 38 and are generally more vulnerable to brain injury than females 39 , our results showing higher sensitivity in females is unexpected and may be reflective of a lower rate of baseline neurogenesis in female rodents 40 , 41 , which is also evident in our data. Remarkably though, the population of newly born neurons in both female and male mice, regardless of radiation dose, rebounded to significantly higher levels than sham-irradiated control levels when assayed later, at 12 months post-exposure.…”
Section: Discussionsupporting
confidence: 61%
“…There may also be dorsal-ventral differences in rates of maturation that are sex-dependent. Adult-born neurons in the dorsal and ventral DG acquired mature neuronal markers faster in males than in females, but adult-born neurons in only the dorsal DG acquired mature morphology faster in males than in females (Yagi et al, 2020).…”
Section: Dorsal-ventral Dentate Gyrusmentioning
confidence: 89%
“…Moreover, most studies have solely used male animals to characterize maturational profiles, but recent work in rats suggests that these results do not generalize to females. For example, although the overall density of mature adult‐born neurons in male and female rats does not differ, multiple studies suggest that male rats exhibit significantly higher levels of proliferation (Barha, Brummelte, Lieblich, & Galea, 2011; Brummelte & Galea, 2010; Hillerer, Neumann, Couillard‐Després, Aigner, & Slattery, 2013; Lagace et al, 2007; Spritzer et al, 2017) and attrition than the female rats, and adult‐born neurons of male rats acquire mature neuronal markers and morphology significantly faster than those of female rats (Yagi et al, 2020), suggesting an accelerated developmental trajectory.…”
Section: Overview Of Maturation and Connectivitymentioning
confidence: 99%
See 1 more Smart Citation
“…Distinct time point of analysis could lead to data variation ( 98 ). A remarkable sex difference was observed in AHN of rodent brains ( 75 , 99 ). Furthermore, data variability may be caused by the sensitivities of antibodies used for detection ( 29 ).…”
Section: Discussionmentioning
confidence: 99%